Multi-Chromophore Dyes for Improving Light Stability of Electro-Fluidic Displays - Deng, Yong; Ye, Dechao; Guo, Yuanyuan; Zhou, Guofu; Jiang, Hongwei (Frontiers in Physics, 2021)
Electro-fluidic display (EFD) is a new reflective display based on electrowetting phenomenon which is applied to the outdoor billboard. Organic dyes are the most important materials for the color gamut and reliability of the EFD devices, which are always synthesized based on mono-chromophore dye in previous work. In this paper, we report our research on azo pyrazolone as the chromophore to construct a polychromic macromolecular dye system. The light stability and photo-electric properties of these new dyes are researched detailed. It is found that the light stability of multi-chromophore dyes and backflow properties are much better than corresponding mono-chromophore dye.